IMPLEMENTATION OF INTERACTIVE MODULE BASED ON LIVEWORKSHEET IN CONSTRUCTING HISTORY LEARNING TO IMPROVE HISTORICAL THINKING OF STUDENTS OF SMA YP UNILA BANDAR LAMPUNG IN 2024 - Maftuchin, Maftuchin; Sinaga, Risma Margaretha; Aransyah, Ade; Brajannoto, Detoprani; Hamzah, Intan (Journal of Research on Language Education, 2025)
This study aims to evaluate the implementation of interactive modules based on Liveworksheet in constructing history learning to improve historical thinking skills and historical awareness of students at SMA Yayasan Pendidikan Universitas Lampung. The method used is descriptive quantitative research involving 64 students as samples. The study was conducted in four meetings, where each meeting lasted for 2x90 minutes. Data were collected through pretest and posttest, which consisted of 10 question items. The results showed a significant increase in student scores, with the highest pretest score of 84 and post-test of 96. Analysis using the N-Gain technique showed that 29.69% of students were in the high category, while 70.31% were in the medium category. These findings indicate that interactive modules based on Liveworksheet are effective in improving students' understanding of history. This study recommends the use of innovative and interactive teaching modules to support a more interesting and effective learning process in the digital era.